One‐Pot Synthesis of Phenylmethanethiolate‐Protected Au20(SR)16 and Au24(SR)20 Nanoclusters and Insight into the Kinetic Control. Issue 11 (10th July 2013) - Zhu, Xiuyi; Jin, Shenshen; Wang, Shuxin; Meng, Xiangming; Zhu, Changwei; Zhu, Manzhou; Jin, Rongchao
Abstract: We report two synthetic routes for concurrent formation of phenylmethanethiolate (‐SCH2 Ph)‐protected Au20 (SR)16 and Au24 (SR)24 nanoclusters in one‐pot by kinetic control. Unlike the previously reported methods for thiolate‐protected gold nanoclusters, which typically involve rapid reduction of the gold precursor by excess NaBH4 and subsequent size focusing into atomically monodisperse clusters of a specific size, the present work reveals some insight into the kinetic control in gold–thiolate cluster synthesis. We demonstrate that the synthesis of ‐SCH2 Ph‐protected Au20 and Au24 nanoclusters can be obtained through two different, kinetically controlled methods. Specifically, route 1 employs slow addition of a relatively large amount of NaBH4 under slow stirring of the reaction mixture, while route 2 employs rapid addition of a small amount of NaBH4 under rapid stirring of the reaction mixture. At first glance, these two methods apparently possess quite different reaction kinetics, but interestingly they give rise to exactly the same product (i.e., the coproduction of Au20 (SCH2 Ph)16 and Au24 (SCH2 Ph)20 clusters). Our results explicitly demonstrate the complex interplay between the kinetic factors that include the addition speed and amount of NaBH4 solution as well as the stirring speed of the reaction mixture. Such insight is important for devising synthetic routes for different sized nanoclusters. We also compared the photoluminescence and electrochemical properties of PhCH2 S‐protected Au20 and Au24 nanoclusters with the PhC2 H4 S‐protected counterparts. A surprising 2.5 times photoluminescence enhancement was observed for the PhCH2 S‐capped nanoclusters when compared to the PhC2 H4 S‐capped analogues, thereby indicating a drastic effect of the ligand that is merely one carbon shorter. Abstract : Everything is under control : Two one‐pot synthetic routes for the concurrent synthesis of Au20 (SCH2 Ph)16 and Au24 (SCH2 Ph)20 nanoclusters under kinetic control were developed (see scheme). The results explicitly demonstrate the complex interplay between the kinetic factors that include the addition speed and amount of NaBH4 solution as well as the stirring speed of the reaction mixture.